Student Responses to Culture-Based Mathematics Learning in the Indonesian and Thailand Education Curricula - Payadnya, I Putu Ade Andre; Wulandar, I Gusti Ayu Putu Arya; Puspadewi, Kadek Rahayu; Saelee, Sompob (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
The aim of this research was to assess how students in Indonesia and Thailand react to ethnomathematics problems within their respective cultures. The participants consisted of 50 students in grades 7 to 12 from Indonesia and Thailand. Descriptive analysis techniques were employed in this study. Data were gathered using questionnaires, tests, and interviews. Subsequently, qualitative descriptive data analysis techniques such as Data Reduction, Data Presentation, Drawing Conclusions, and Verification were applied to analyze the collected data. The results showed that students presented positive responses to the given ethnomathematical problems. From the results of the questionnaire, about 76% showed an average very positive response to ethnomathematics, while the remaining 24% of students showed a moderately positive response to ethnomathematics. From the interview, students stated that students assume that ethnomathematics is interesting and challenging. Students’ answers to the ethnomathematics test showed that they were unable to understand ethnomathematics and tended to work on planning and finally got the wrong results. This is because students who pay less attention to their cultural environment tend to acquire procedural mathematics learning. Therefore, teachers are expected to be able to develop more realistic mathematics learning by linking mathematical concepts with the real world.